Trigonometry (11th Edition) Clone

Published by Pearson
ISBN 10: 978-0-13-421743-7
ISBN 13: 978-0-13421-743-7

Appendix A - Equations and Inequalities - Page 420: 31



Work Step by Step

$x^{2}-5x+6=0$ $x^{2}-2x-3x+6=0$ $x(x-2)-3(x-2)=0$ $(x-2)(x-3)=0$ $(x-2)=0$ or $(x-3)=0$ $x=2$ or $x=3$ Check: Substituting $x=2$ in the equation, $(2)^{2}-5(2)+6=0$ $4-10+6=0$ $-6+6=0$ $0=0$ Substituting $x=3$ in the equation, $(3)^{2}-5(3)+6=0$ $9-15+6=0$ $-6+6=0$ $0=0$ Both values check and the solution set is {$2,3$}.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.